2019
DOI: 10.1016/j.pmrj.2018.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Varying Corticosteroid Type, Dose, and Volume for the Treatment of Pain in Small‐ and Intermediate‐Size Joint Injections: A Narrative Review

Abstract: Objective To systematically evaluate the scientific literature examining the effect of corticosteroid type, dose, and volume of small‐ and intermediate‐size joint injections on pain and function. Type Narrative review. Literature Survey Medline (PubMed), Cochrane Central Register of Controlled Trial, and SportDiscus databases were searched. Methodology Inclusion criteria included prospective studies evaluating pain‐ and/or function‐related improvements following a corticosteroid injection of a small‐ or interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
(65 reference statements)
0
14
0
1
Order By: Relevance
“…Treatment with 20mg or 40mg of TH produced equal relapse after six months in patients with chronic polyarthritis and when treating medium-sized joints. With that in mind, since no difference in outcome was found between the compared doses, the authors advised that lower dose should be preferred, reducing pharmaceutical costs and metabolic side effects [71,72]. As a whole, these reports present the overall safety and effectiveness of IA TH in the management of OA, measured with multiple validated CMI and other clinical evaluations.…”
Section: Plos Onementioning
confidence: 99%
“…Treatment with 20mg or 40mg of TH produced equal relapse after six months in patients with chronic polyarthritis and when treating medium-sized joints. With that in mind, since no difference in outcome was found between the compared doses, the authors advised that lower dose should be preferred, reducing pharmaceutical costs and metabolic side effects [71,72]. As a whole, these reports present the overall safety and effectiveness of IA TH in the management of OA, measured with multiple validated CMI and other clinical evaluations.…”
Section: Plos Onementioning
confidence: 99%
“…Side effects observed with intra articular steroid injections are local skin pigment changes, subcutaneous fat wasting, tendon rupture, and systemic involvement, but are very rare [21]. A recent systematic review that examined the effectiveness of injected corticosteroid for treatment of pain in small and intermediate size joints showed that 10-20 mg of methylprednisolone or triamcinolone injections are the most common steroids used for small joint pain [22]. A few studies in this review examined the MCP and IP joints and results showed that corticosteroid injections provided significant pain relief that lasted for several weeks up to several months; one study in particular for the IP joints showed that triamcinolone injections compared to methylprednisolone had greater improvements in patient-reported pain and functionality [21,22].…”
Section: Injection Techniquementioning
confidence: 99%
“…A recent systematic review that examined the effectiveness of injected corticosteroid for treatment of pain in small and intermediate size joints showed that 10-20 mg of methylprednisolone or triamcinolone injections are the most common steroids used for small joint pain [22]. A few studies in this review examined the MCP and IP joints and results showed that corticosteroid injections provided significant pain relief that lasted for several weeks up to several months; one study in particular for the IP joints showed that triamcinolone injections compared to methylprednisolone had greater improvements in patient-reported pain and functionality [21,22]. Recently, Wang et al found that using 20 mg of triamcinolone acetonide (TA), double the dose generally used for small joint RA, for the MCP and PIP joints combined with US for increased accuracy of injections, was very effective for treating refractory pain and swelling while having less side effects and having no implications on the original RA treatment plan that normally is comprised of DMARD's and biologics [23].…”
Section: Injection Techniquementioning
confidence: 99%
“…In the setting of advanced degenerative changes of the radiocarpal joints, patients often experience considerable limitations in ADLs that are resistant to nonsurgical treatment. 52 , 53 , 54 If the degenerative changes spare the midcarpal articulations, RL and RSL arthrodesis represent promising options for patients to improve pain and function. 6 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 47 Compared with TWA, 20 , 55 , 56 RL and RSL arthrodesis maintain wrist motion at or above the level of functional wrist motion required to perform most ADLs.…”
Section: Discussionmentioning
confidence: 99%